Behind the Hashtag: Online Disclosure of Mental Illness and Community Response on Tumblr. - Griffith, Frances J.; Stein, Catherine H. (American Journal of Community Psychology, 2021)
The present study examined personal disclosures about mental illness and the responses of online community members on the social media platform, Tumblr. We sampled public blog posts of 14,626 Tumblr users disclosing ten different mental health diagnoses using hashtags (e.g., #depression, #anxiety, and #anorexia). We examined the content of users' disclosures, predictors of disclosure frequency, and predictors of online community response. The content of most disclosures was related to users' emotions and cognitions about their mental health and their feelings of interpersonal loss and change over time. Content varied with users' disclosure frequency and with self‐identified mental health diagnoses. Predictors of disclosure frequency included the "self effects" of writing about oneself or one's opinions, such as self‐concept formation, and "reception effects" of receiving responses to one's writing. User disclosures generally increased with frequency of community response (reception effects), and the degree of this effect differed depending on the disclosed diagnosis (self effects). The responses of online community members also varied significantly across disclosed diagnoses. The implications of our findings for community research and action are discussed. Highlights: People with mental illness may disclose information on social media to build social capital.Mental health disclosures included themes of emotions, interpersonal loss, and change.Disclosure frequency increased with community responses in interaction with diagnosis.Community responses varied as a function of mental health diagnosis disclosed.